Whole exome sequencing highlights variants in association with Keratoconus in Jordanian families - Tawfiq Froukh; Ammar Hawwari; Khalid Al Zubi (BMC, 2020)
Abstract Background Keratoconus (KC) is usually bilateral, noninflammatory progressive corneal ectasia in which the cornea becomes progressively thin and conical, resulting in myopia, irregular astigmatism, and corneal scarring. Methods Eight families characterized by consanguineous marriages and/or multiple keratoconic individuals were examined genetically. Whole exome sequencing was done as trio or quadro per family. The output of the filtration procedure, based on minor allele frequency (MAF) less than 0.01 for homozygous variants and MAF equals 0 for heterozygous variants, is 22 missense variants. Results Based on the gene/protein function five candidate variants were highlighted in four families. Two variants were highlighted in one family within the genes MYOF and STX2, and one variant is highlighted in each of the other three families within the genes: COL6A5, ZNF676 and ZNF765. Conclusion This study is one of the very rare that highlights genetic variants in association with KC.